Comparación del alcohol isopropilico y la acetona para la deshidratación en la técnica de plastinación, como método de conservación anatómica en feto bovino (monografía) (2022)
One of the most useful methods for studying anatomical structures is the use of cadaveric preparations preserved in formalin, since students can grasp and retain the information for a longer time, which is beneficial for the future of the professional (Brave, 2006). Despite the advantages of this practice, alternatives to the use of pieces fixed with formaldehyde, by the vapors that these emanate and that can represent a risk for students and veterinary personnel since they have an irritant, allergenic and probably carcinogenic (Morales, Pérez and Severiche, 2014).